(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This contribution provides a study of the Antonines of the General Preceptory of Ranverso, their activities in Val di Susa and their properties on the Piccolo Moncenisio between the 13th and the 15th century. The investigation was based on published studies (especially those by Italo Ruffino) and on documents and archival inventories examined in the light of new interpretations of the history of the Antonines in particular and of late medieval hospitals in general. Putting aside the theory of the canons of St Anthony as skilled nurses, the history of the hospital of Ranverso can be re‐interpreted as that of the centre of an agricultural enterprise whose possessions extended as far as the Moncenisio. From the study of the contemporary, but also later and indirect sources, it is clear that the management of unattended pastures was problematic and that the order was often unable to claim its property or grazing rights due to poor record keeping.